ROLE OF CLINICAL PHARMACIST IN CLINICAL AUDIT AT DEPARTMENT OF GENERAL MEDICINE - Tasleem, P.; Reshma, M.; Kiran, M. Sai; Reddenna, L.; Sreedhar, V. (Journal of Biomedical and Pharmaceutical Research, 2021)
Background of the study: Inaccuracy in writing and poor legibility of handwriting or incomplete writing of a prescription can lead to misinterpretation, thus leading to errors in dispensing and administration. Both individual and system related factors are responsible for prescribing errors. Recognition is the essential step in building safer systems and preventing errors. These errors can be detected by systematic analysis of prescriptions through a prescription audit. Hence, this project was proposed to improve the prescription practice by recommending the prescribing and therapeutic interventions in a selected setting of Anantapur. Research Methodology: The study was approved by the ethical committee of the hospital. Before starting the study, the researcher obtained formal permission from Government General Hospital, Anantapuramu. The data collection period was for 6 months. A prospective observational design was adopted for this study. The prescriptions were selected on the basis of inclusion criteria. Descriptive statistics like frequency and percentage were calculated to describe the data. Results and discussion: The overall observation made from this study was that clinical pharmacist could identify some drug related problems, provides clinical pharmacy services and contribute to better patient care being a part of the healthcare team. Conclusion: There is enormous scope for the clinical pharmacist to play an important role in health care in various aspects like monitoring ADRs, provision of drug information, identifying DRPs and patient counseling which will bring better patient outcome. Key words: Adverse drug reactions, Clinical audit, Clinical Pharmacist, prescription audit